2013 IEEE International Conference on Control System, Computing and Engineering 2013
DOI: 10.1109/iccsce.2013.6719971
|View full text |Cite
|
Sign up to set email alerts
|

A review of Genetic Algorithms and Parallel Genetic Algorithms on Graphics Processing Unit (GPU)

Abstract: Genetic Algorithms (GAs) is proven to be effective in solving many optimization tasks. GAs is one of the optimization tools used widely in solving problems based on natural selection and genetics. This paper is intended to cover the study of GA and parallel GA and analyses its usage in CPU and GPU. One of the popular ways to speed up the processing time was by running them as parallel. The idea of parallel GAs may refer to an algorithm that works by dividing large problem into smaller tasks. Broad literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…From the previous paper work [4,5], it is observed that Parallel Genetic Algorithm can be easily map on GPU than other prediction algorithms. Time required to find fitness function is very less than to find mapping function in SVM.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the previous paper work [4,5], it is observed that Parallel Genetic Algorithm can be easily map on GPU than other prediction algorithms. Time required to find fitness function is very less than to find mapping function in SVM.…”
Section: Observationsmentioning
confidence: 99%
“…[3] Some common tools for prediction include: neural networks, regression, Support Vector Machine (SVM), and discriminant analysis. Recently, data mining techniques such as neural networks, fuzzy logic systems, genetic algorithms and rough set theory are used to predict control and failure detection tasks [4]. In this paper, the algorithms will forecast a probability for the given data situation.…”
Section: Prediction Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid a search method of genetic algorithm can improve the search performance. Fauzi Mohd Johar, Farah Ayuni Azminand et al [9] studies GA and parallel GA and analyses its usage in central Processing Unit (CPU) and Graphics Processing Unit (GPU).…”
Section: Performance Of Gamentioning
confidence: 99%
“…They discussed the features of the GPU and the relevant issues when implementing parallel genetic algorithms. Johar et al [13] conducted an analysis of genetic algorithms implemented in parallel both CPU and GPU using CUDA [14] architecture. The analysis was performed by comparing the operations performed in both implementations.…”
Section: Introductionmentioning
confidence: 99%